Effects of food material properties and embedded status on food processing efficiency in bearded capuchins. Issue 4 (24th May 2022) - Chalk‐Wilayto, Janine; Fogaça, Mariana Dutra; Wright, Barth W.; van Casteren, Adam; Fragaszy, Dorothy M.; Izar, Patricia; Visalberghi, Elisabetta; Strait, David S.; Ross, Callum F.; Wright, Kristin A.; Laird, Myra F.
Abstract: Objectives: Capuchin monkeys ( Cebus spp. and Sapajus spp.) routinely extract food resources that are embedded in protective matrices. Features such as relative brain size, manual dexterity, and — in the case of Sapajus spp .— a robust feeding system are considered adaptations for accessing embedded foods. Compared with adults, juvenile capuchins exhibit reduced food processing efficiency when processing embedded foods. Although this reduced efficiency has been attributed to inexperience or lack of strength when processing embedded foods, little is known about how food material properties (FMPs) relate to age‐related changes in feeding efficiency. Materials and methods: We used data collected from three groups of Sapajus libidinosus to test relationships between feeding efficiency and FMP variation when processing embedded and nonembedded foods. Feeding efficiency was defined in three ways: (i) duration, (ii) frequency, and (iii) variation in sequence of food processing behaviors. Results: We found limited support for an effect of FMPs and age on feeding sequence durations or on processing behavior frequency. Number of unique behavioral patterns was negatively correlated with age. Embedded foods elicited longer durations, higher behavioral frequencies and more unique behaviors compared to nonembedded foods. Discussion: Results indicate FMP variation impedes some measures of juvenile food processing efficiency. Foods with high stress‐limited indices reduced some measures of processing efficiency in juveniles. These data are consistent with prior studies of juvenile capuchin feeding competency when exploiting embedded foods and suggest skill development may be a relatively more important constraint for overall juvenile feeding efficiency than body size or strength.